Proteins and Glycoproteins of Paramyxoviruses: a Comparison of Simian Virus 5, Newcastle Disease Virus, and Sendai Virus - Mountcastle, Walter E. (1971)
The polypeptides of three paramyxoviruses (simian virus 5, Newcastle disease virus, and Sendai virus) were separated by polyacrylamide gel electrophoresis. Glycoproteins were identified by the use of radioactive glucosamine as a carbohydrate precursor. The protein patterns reveal similarities among the three viruses. Each virus contains at least five or six proteins, two of which are glycoproteins. Four of the proteins found in each virus share common features with corresponding proteins in the other two viruses, including similar molecular weights. These four proteins are the nucleocapsid protein (molecular weight 56,000 to 61,000), a larger glycoprotein (molecular weight 65,000 to 74,000), a smaller glycoprotein (molecular weight 53,000 to 56,000), and a major protein which is the smallest protein in each virion (molecular weight 38,000 to 41,000).